Improving cyclic performance of Si anode for lithium-ion batteries by forming an intermetallic skin1. Issue 48 (28th May 2015) - Huang, Xingkang; Mao, Shun; Chang, Jingbo; Hallac, Peter B.; Fell, Christopher R.; Luo, Yanting; Metz, Bernhard; Jiang, Junwei; Chen, Junhong
<x xml:space="preserve">Abstract</x> A chemically bonded NiSix layer was coated on the Si anode surface for enhancing cyclic performance of the Si anode.